Barbarian's heart - Dixon, Ruby, 1976- (Dixon, Ruby, 1976- Ice planet barbarians series., 2025)
"The next novel in the Ice Planet Barbarians series, an international publishing phenomenon-now in a special print edition with bonus material! The unthinkable happens when a devastating accident causes Pashov to forget his mate, but Stacy will do whatever it takes to make her family whole again.... I've never spent a day without my mate since arriving on the ice planet. I'm happy and in love, and we have a beautiful child together. All that changed when the world shook. My mate nearly died. He wakes up from his coma ... and he can't remember me. Or our son. Every memory of the past two years is gone. And that changes everything between us. How can I love someone that doesn't remember me? How can I not, when I know he's still my mate underneath it all?"--